2002
DOI: 10.2105/ajph.92.12.1964
|View full text |Cite
|
Sign up to set email alerts
|

Battering Victimization Among a Probability-Based Sample of Men Who Have Sex With Men

Abstract: Rates of battering victimization among urban MSM are substantially higher than among heterosexual men and possibly heterosexual women. Public health efforts directed toward addressing intimate partner battering among these men are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
226
8
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(266 citation statements)
references
References 21 publications
18
226
8
14
Order By: Relevance
“…In relation to victimization, 28.6% of the participants reported the occurrence of minor physical abuse without sequelae, 11.9% reported severe physical abuse without sequelae, 10.7% reported minor physical abuse with sequelae and 1.2% reported severe physical abuse with sequelae. Although the studies developed in this area generally do not seek to distinguish between physical abuse with sequelae and physical abuse without sequelae, it is possible to see similarities in their prevalence rates, which range between 7.9% and 31% (Antunes & Machado 2005;Costa et al, 2009;Edwards & Sylaska, 2013;Finneran & Stephenson, 2013;Halper et al, 2004;Houston & McKirnan, 2007;Matte & Lafontaine, 2011;Pantalone et al, 2012;Ramachandran et al, 2010;Turell, 2000;Yu et al, 2013), as well as differences, as the rates found in this study are lower than the results of other studies that report rates between 45.1% and 89.9% (Blosnich & Bossarte, 2009;Craft & Serovich, 2005;Greenwood et al, 2002). Again, the social stigma of domestic violence may contribute to explaining the lower volume of reports of this type of abuse by participants (Paiva & Figueiredo, 2005).…”
Section: Discussioncontrasting
confidence: 46%
“…In relation to victimization, 28.6% of the participants reported the occurrence of minor physical abuse without sequelae, 11.9% reported severe physical abuse without sequelae, 10.7% reported minor physical abuse with sequelae and 1.2% reported severe physical abuse with sequelae. Although the studies developed in this area generally do not seek to distinguish between physical abuse with sequelae and physical abuse without sequelae, it is possible to see similarities in their prevalence rates, which range between 7.9% and 31% (Antunes & Machado 2005;Costa et al, 2009;Edwards & Sylaska, 2013;Finneran & Stephenson, 2013;Halper et al, 2004;Houston & McKirnan, 2007;Matte & Lafontaine, 2011;Pantalone et al, 2012;Ramachandran et al, 2010;Turell, 2000;Yu et al, 2013), as well as differences, as the rates found in this study are lower than the results of other studies that report rates between 45.1% and 89.9% (Blosnich & Bossarte, 2009;Craft & Serovich, 2005;Greenwood et al, 2002). Again, the social stigma of domestic violence may contribute to explaining the lower volume of reports of this type of abuse by participants (Paiva & Figueiredo, 2005).…”
Section: Discussioncontrasting
confidence: 46%
“…Using the score stratification system to classify the studies according to their final scores, only one study (Greenwood et al, 2002) was deemed acceptable, with a final score of at least 70%. Fifteen studies were deemed adequate, with final scores ranging between 40% and 69% (Balsam et al, 2005;T.…”
Section: Resultsmentioning
confidence: 99%
“…Using the score stratification system to classify the studies according to their final scores, only one study (Greenwood et al, 2002) was deemed acceptable, with a final score of at least 70%. Fifteen studies were deemed adequate, with final scores ranging between 40% and 69% (Balsam et al, 2005; T. W. Burke et al, 2002;Craft & Serovich, 2005;Fortunata & Kohn, 2003;Heintz & Melendez, 2006;McClennen, Summers, & Daley, 2002;McClennen, Summers, & Vaughan, 2002;Merrill & Wolfe, 2000;Miller, Greene, Causby, White, & Lockhart, 2001;Owen & Burke, 2004;Regan, Bartholomew, Oram, & Landolt, 2002;Scherzer, 1998;Telesco, 2003;Toro-Alfonso & Rodriguez-Madera, 2004b;Waldner-Haugrud, Gratch, & Magruder, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Interviews covered a range of social, psychological, and behavioral phenomena related to HIV. Major sections of the survey instrument included questions about the gay community (involvement, services used, attitudes toward) (Barrett & Pollack, 2005), demographic characteristics (Catania et al, 2006), attendance at gay venues ("places where men go to meet and socialize with other men") Woods et al, 2003), sexual behavior (both a "global" and partner-by-partner assessment), sexual development, including the "coming out" process (Barrett, Pollack, & Tilden, 2002), experiences with harassment and violence (including adverse familial events, anti-gay victimization, sexual coercion, and partner violence) (Arreola, Neilands, Pollack, Paul, & Catania, 2005;Greenwood et al, 2002;Relf, Huang, Campbell, & Catania, 2004),sexual problems, depression, and suicidal ideation (Mills et al, 2004;Paul et al, 2002), substance use (Klitzman, Greenberg, Pollack, & Dolezal, 2002;Stall et al, 2001aStall et al, , 2003, HIV testing and serostatus (Osmond et al, 2000;Stall et al, 2001b), and AIDS care-giving.…”
Section: Methodsmentioning
confidence: 99%